The Relationship between Self-Efficacy in Choosing Nutritious Foods and the Daily Consumption Practices of Pregnant Women - Asri Masitha Arsyati; Nhadira Nhestricia; Agustina Agustina (Universitas Islam Negeri Sumatera Utara, Medan, 2026)
Adequate consumption of nutritious food by pregnant women is a crucial factor in supporting maternal health and fetal growth and development. However, various factors such as knowledge, self-efficacy, and social support can influence the daily consumption behavior of pregnant women. This issue remains a public health challenge in Indonesia, mainly due to various behavioral, social, and environmental factors. This study aims to analyze the factors that affect the daily consumption of pregnant women in Bogor City Indonesia. An observational analytical study with a cross-sectional design was conducted on 231 pregnant women. The relationship between variables was analyzed using the Chi-Square statistical test with a p-value <0.05 as the significance threshold. Mothers' self-efficacy in choosing nutritious foods is significantly related to daily consumption adequacy (p = 0.000; OR = 0.319). Nutritional knowledge also shows a significant relationship (p = 0.016; OR = 2.043). Family social support has a significant effect on the daily consumption of pregnant women (p = 0.008; OR = 2.780). Meanwhile, food access (p = 0.978; OR = 0.976), antenatal nutrition counseling (p = 0.148; OR = 0.648), access to pregnancy nutrition information media (p = 0.116; OR = 2.872), and cultural/food taboo practices (p = 0.246; OR = 0.644) do not show a significant relationship. Self-efficacy, nutrition knowledge, and family social support are factors that significantly influence the adequacy of daily consumption among pregnant women. Efforts to improve nutrition education and strengthen family support should be the focus of interventions aimed at encouraging healthy eating behaviors among pregnant women Keywords: Food Consumption, Nutritional Knowledge, Pregnant Women, Self-Efficacy